2015
DOI: 10.1371/journal.pone.0145867
|View full text |Cite|
|
Sign up to set email alerts
|

Unilateral Left-Hand Contractions Produce Widespread Depression of Cortical Activity after Their Execution

Abstract: The execution of unilateral hand contractions before performance has been reported to produce behavioral aftereffects in various tasks. These effects have been regularly attributed to an induced shift in activation asymmetry to the contralateral hemisphere produced by the contractions. An alternative explanation proposes a generalized state of reduced bilateral cortical activity following unilateral hand contractions. The current experiment contrasted the above explanation models and tested the state of cortic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
50
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(56 citation statements)
references
References 72 publications
5
50
0
1
Order By: Relevance
“…Left-hand contractions have been proposed to prime the visuospatial processes of the right hemisphere necessary for motor performance and to suppress the analytical processes of the left hemisphere linked to the step-by-step control of skill execution (Beckmann et al, 2013;Cross-Villasana, Gröpel, Doppelmayr, & Beckmann, 2015). In all five studies on left-hand contractions, researchers (e.g.…”
Section: Self-focus-based Interventionsmentioning
confidence: 99%
“…Left-hand contractions have been proposed to prime the visuospatial processes of the right hemisphere necessary for motor performance and to suppress the analytical processes of the left hemisphere linked to the step-by-step control of skill execution (Beckmann et al, 2013;Cross-Villasana, Gröpel, Doppelmayr, & Beckmann, 2015). In all five studies on left-hand contractions, researchers (e.g.…”
Section: Self-focus-based Interventionsmentioning
confidence: 99%
“…Left-hand dynamic handgrip activates motor centers of the right hemisphere during the hand clenching [24,25]. Consequently, an increase in high Alpha is observed that spreads across the whole scalp [26]. High Alpha has an inhibitory function and can be said to and produces a state of cortical relaxation after the clenching.…”
Section: Introductionmentioning
confidence: 99%
“…High Alpha has an inhibitory function and can be said to and produces a state of cortical relaxation after the clenching. This involves a reduction of the dominant left-hemispheric activation [26]. The state of cortical relaxation after clenching the left (compared to right) hand is likely due to the higher level of connectivity and white matter in the right hemisphere (which controls the left hand), compared to the remaining parts of the brain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The above evidence implies that a persistent left-hemispheric dominance may be linked to choking, whereas a symmetrical brain activation may underlie superior, skilled performance, which has been supported by Beckmann et al (2013) who primed the right hemisphere using left-hand contractions immediately prior to skill execution under pressure. Based on research demonstrating that people's right and left hand are mainly controlled via the contralateral brain hemisphere (Kim et al, 1993) Gröpel, Doppelmayr, & Beckmann, 2015). Thus, symmetrical brain activation patterns during skill execution under pressure leads to less likelihood of choking because there is less activation of the verbal-analytic centers and less conscious attention that interferes with automatic movement execution.…”
Section: An Investigation Into Handedness and Choking Under Pressure mentioning
confidence: 99%